Comparative ocean governance : place-based protections in an era of climate change - Craig, Robin Kundis (Cheltenham, UK : Edward Elgar, 2012)
Comparative Ocean Governance examines how the drive to improve governance of the oceans through place-based management - such as marine protected areas, ecosystem-based management, and ocean zoning - can be adapted to a world already experiencing the impacts of climate change. The author discusses the value of and the threats facing the world's oceans, the international law regimes that support place-based management, and the general promotion of place-based management to improve prior ocean governance. She concludes by suggesting three approaches to incorporating climate change adaptation into place-based marine governance, using current examples from around the world.
Part I. The ocean and the threats to it. The value of the oceans ; Non-climate threats to marine ecosystems and biodiversity ; Climate change and the oceans -- Part II. Ocean governance, international law, and place-based protections for marine ecosystems. The international legal framework of ocean governance ; Place-based marine governance: an overview -- Part III. Adapting place-based marine governance to climate change.'Accidental' adaptation : climate change and existing place-based marine management ; Purposeful climate change adaptation in place-based governance systems ; Making marine spatial planning climate change dynamic.
Includes bibliographical references (pages ix-xi) and index.
Keywords: Marine resources conservation -- Law and legislation; Marine resources conservation -- International cooperation; Marine resources development -- Law and legislation; Marine resources -- Government policy; Law of the sea; Climatic changes -- Law and legislation; Climatic changes -- Government policy